2021
DOI: 10.1093/ve/veab085
|View full text |Cite
|
Sign up to set email alerts
|

In action—an early warning system for the detection of unexpected or novel pathogens

Abstract: Pro-active approaches in preventing future epidemics include pathogen discovery prior to their emergence in human and/or animal populations. Playing an important role in pathogen discovery, high-throughput sequencing (HTS) enables the characterization of microbial and viral genetic diversity within a given sample. In particular, metagenomic HTS allows the unbiased taxonomic profiling of sequences; hence, it can identify novel and highly divergent pathogens such as viruses. Newly discovered viral sequences must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…mNGS is characterized by a constant and ultra-rapid development of new analytical methods, both biological and bioinformatics, that seem better suited to follow the dynamic of pandemic events and in general viral outbreaks. This suggests the opportunity to implement these technologies to establish early warning systems [74] and to design effective disease control and prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…mNGS is characterized by a constant and ultra-rapid development of new analytical methods, both biological and bioinformatics, that seem better suited to follow the dynamic of pandemic events and in general viral outbreaks. This suggests the opportunity to implement these technologies to establish early warning systems [74] and to design effective disease control and prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the component of mosquito virome and the high abundance of viruses in mosquitoes can be revealed using metagenomic sequencing (Metsky et al, 2019;Ramıŕez et al, 2020). Moreover, metagenomic sequencing is also of great significance for the discovery and identification of novel viruses (Sadeghi et al, 2018;Santos et al, 2021). Many mosquito species virome studies applying NGS tools identified new viruses and described their diversity, which led to the discovery of insect-specific viruses (Romo et al, 2018;Chenyan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Illumina sequencing combined with bioinformatics analysis is more likely to be effective than traditional methods ( Zhang et al., 2018 ; Marzoli et al, 2021 ; Thannesberger et al., 2021 ). Moreover, a lot of viruses derived from numerous species have been detected using this approach ( Sadeghi et al., 2018 ; Santos et al., 2021 ). Therefore, the composition of the pangolin virome can be revealed using Illumina sequencing.…”
Section: Discussionmentioning
confidence: 99%